2017
DOI: 10.3389/fmicb.2017.02179
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Insight into the Relationship between Soil Microbial Community and Tobacco Bacterial Wilt Disease

Abstract: The soil microbial communities play an important role in plant health, however, the relationship between the below-ground microbiome and above-ground plant health remains unclear. To reveal such a relationship, we analyzed soil microbial communities through sequencing of 16S rRNA gene amplicons from 15 different tobacco fields with different levels of wilt disease in the central south part of China. We found that plant health was related to the soil microbial diversity as plants may benefit from the diverse mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 65 publications
7
60
1
Order By: Relevance
“…Shi et al 69 observed that microbial diversity decreased as network size and connectivity increased, which resulted in an increased community organisation. It has also been shown that more complex networks are able to cope with environmental changes 76 , increase crop productivity 73 or suppress soil borne pathogen infection on plants 77 . Indeed, semi-dwarf wheat cultivars carrying Rht alleles were previously shown to be more susceptible than wild cultivars to initial infection by some pathogens 78,79 .…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al 69 observed that microbial diversity decreased as network size and connectivity increased, which resulted in an increased community organisation. It has also been shown that more complex networks are able to cope with environmental changes 76 , increase crop productivity 73 or suppress soil borne pathogen infection on plants 77 . Indeed, semi-dwarf wheat cultivars carrying Rht alleles were previously shown to be more susceptible than wild cultivars to initial infection by some pathogens 78,79 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, complex networks contribute to better cope with environmental changes or to suppress soilborne pathogens. For instance, tobacco plants associated with rhizosphere microbial communities exhibiting complex networks showed lower incidence of bacterial wilt disease compared to plants associated with communities displaying less connections in their networks [29]. Also, in Brassica napus L. seeds microbiome, tightly-knit and complex microbial networks have been observed and proposed as traits that make the invasion by newcomers (either beneficial or pathogenic) of these niches difficult [55].…”
Section: Discussionmentioning
confidence: 99%
“…3). Co-occurrence interaction studies have been mainly focused on rhizosphere and phyllosphere microhabitats [29,30]. To the best of our knowledge, we have implemented for the first time this approach to assess a root endosphere community and the topological modifications occurring in this microhabitat upon the introduction of a soilborne pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinobacteria phylum, which although were not abundant in the communities, had an important role 475 within co-occurence networks. Phylum Actinobacteria was found previoulsy as a key taxon on 476 bacterial soil networks, where it could reduce the chance of soil plant pathogen invasion for tobacco 477 bacterial wilt disease (Yang et al 2017b). The decrease of connectivity values has also been observed 478 on soil bacterial communities due to land use, where higher density of links were found in natural 479 forest soils than pasture or field and plantations soils (Lupatini et al 2014), so that maize addition 480 could be considered as a strong perturbaction of soil microbial co-occurrence networks.…”
Section: Discussion 397mentioning
confidence: 99%